COLLOCATION IN THE MOVIE ENTITLED COCO BY MOLINA AND MATTHEW ALDRICH - Linda Sari (Universitas PGRI Palembang, 2019)
AbstractThis research is concerned with collocation in the movie subtitle Coco by Molina and Matthew Aldrich. This research is a descriptive qualitative study. It is supposed to identify the English collocation found in Coco movie; to classify the types of collocation found in Coco movie; and to discuss the meanings of collocation found in Coco movie. In data collection, the research employed triangulation that presented three different techniques, namely documentation, observation and interview. Based on the findings, it is shown that there were 134data of grammatical collocations found in the movie, which consisted of 7 types of grammatical collocations. They were 1 datum of noun+preposition combination, 2 data of noun+to+infinitive, 1 datum of noun+that+clause, 7 data of preposition+noun, 3 data of adjective+preposition combinations, 4 data of predicate adjective+to+infinitive, and 116 data of collocation verb patterns.Keywords: Collocation, Types of Collocation, Subtitle, Classify.